Mediating Role of Employee Motivation in Relationship to Post-Selection HRM Practices and Organizational Performance - Dar, Aftab Tariq; Bashir, Mohsin; Ghazanfar, Faheem; Abrar, Muhammad (International Review of Management and Marketing, 2014)
<!–[if gte mso 9]> 800x600 <![endif]–> The purpose of this cross-sectional study was to explore the meditating role of employee motivation in the relationship between post-selection Human Resource Management (HRM) practices and perceived performance of Islamic Banks operating in Pakistan. This study was based on primary data collected from 200-employees of different Islamic banks in Pakistan by distributing structured and reliable questionnaires. The demographic profile of respondents was diversified in terms of their grade, age, experience and education. Results of correlation analysis revealed that training & development(r = .829), performance evaluation system(r = .752), career development system(r = .666), extrinsic rewards(r = .921), intrinsic rewards (r = .852) and employee motivation(r =.722) have strong positive association with perceived performance of Islamic banks in Pakistan. Results of hierarchical regression analysis supported that post-selection HRM practices have positive impact on perceived organizational performance and employee motivation acts as mediator in the relationship between post-selection HRM practices and perceived organizational performance. Proper implementation of post-selection HRM practices makes employee motivated that resulted in improved organizational performance. Management of Islamic banks desiring optimum performance should pay special attention to need-based training programs, merit-based performance appraisal system, development of progressive career paths, performance-based extrinsic and intrinsic rewards management. While making HRM policies, employee motivation should be given paramount importance as the results of contemporary studies supported that it is the major contributing factor of higher organizational performance. Keywords: Post-Selection Human Resource Management Practices; Employee Motivation; Perceived Organizational Performance; Islamic Banking Sector of Pakistan. JEL Classifications: L25; M12; M51; M52; M53; O15 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman"; –> <!–[endif] –>